Pengaruh Tingkat Bagi Hasil, NPF dan DPK Bagi Profitabilitas Pada PT. Bank Muamalat Indonesia - Dwi Lestari, Ervina; Trimulato, Trimulato; Ismawati, Ismawati; Nuringsih, Nuringsih (Disclosure: Journal of Accounting and Finance, 2023)
This study aims to examine the effect of Third Party Funds, Non-Performing Finance (NPF), and Profit-Sharing Rates on profitability (ROA) at Bank Muamalat Indonesia. This research uses quantitative methods. Sampling using a probability sampling method, the method by which the sample is taken is using a simple random sampling technique. The data used is secondary data obtained from the annual report at Bank Muamalat Indonesia for the period 2008-2020. The analysis used in this study is multiple linear regression analysis. The results show partially that the Third Party Fund variable has a significant negative effect on profitability (ROA), Non- Performing Finance (NPF) has no significant effect on profitability (ROA), Profit Sharing Rate has a positive effect on profitability (ROA), and Profit-Sharing Rate as the dominant variable on the influence of bank profitability.